2015
DOI: 10.1016/j.molbiopara.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a phospholipid hydroperoxide glutathione peroxidase gene from a blood fluke Schistosoma japonicum

Abstract: Phospholipid hydroperoxide glutathione peroxidase (PHGPx) is a major antioxidant enzyme and plays critical roles in the protection of cells against oxidative stress by catalysing reduction of lipid hydroperoxides. A full-length cDNA sequence corresponding to GPx gene from Schistosoma japonicum (designated SjGPx) was isolated and characterized. SjGPx contained an in-frame TGA codon for selenocysteine (Sec) and a concurrent Sec insertion sequence in its 3'-untranslated region. Protein encoded by SjGPx demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…These enzymes are engaged in decomposing lipid hydroperoxides. It was reported that protein levels and enzymatic activity of phospholipid hydroperoxide glutathione peroxidase from Schistosoma japonicum can be stimulated by incubation of adult worms with millimolar amounts of oxidative molecules, such as paraquat or hydrogen peroxide25.…”
Section: Resultsmentioning
confidence: 99%
“…These enzymes are engaged in decomposing lipid hydroperoxides. It was reported that protein levels and enzymatic activity of phospholipid hydroperoxide glutathione peroxidase from Schistosoma japonicum can be stimulated by incubation of adult worms with millimolar amounts of oxidative molecules, such as paraquat or hydrogen peroxide25.…”
Section: Resultsmentioning
confidence: 99%